PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP RETENSI KARYAWAN (Studi Kasus Pada PT. Interaktif Media Siber) - Khairul Bahrun; Muhamat Yusuf (UM. Bengkulu, 2022)
This study entitled the effect of compensation and job satisfaction on employee retention at PT. Interaktif Media Siber.. The formulation of the problem in this study is hom the effect of compensation and job satisfaction on employee retention at PT. Interaktif Media Siber.. The purpose of this study is to determine the effect of compensation and job satisfaction on employee retention at PT. Interaktif Media Siber. This research was conducted for l month, starting on January 15, 2021 and completed on February 15, 2022. The population of this study wes all employees at PT. Cyber Media Interactive, totaling 40 people. The results showed that respondents’ perceptions of Compensation (X1) and Job Satisfaction (X2) had an effect on Employee Retention (Y) with multiple linear regression results with the following equation: Y = 3.782 + 0.406 (X1) + 0.724 (X2) And the coefficient of determination of R2 = 0.943 or approximately (94.3%) through hypothesis testing together (simultaneously) and individually (partial) in this study using the f-test and t test, Compensation (X1) and Job Satisfaction (X2) on Employee Retention (Y) that is = (308,712 > 2,249) and (sig = 0.000 < 0.050), Thus it can be concluded that H3 is accepted, meaning that simultaneously the Compensation (X1) and Job Satisfaction (X2) variables have a significant effect on Employee Retention (Y). Keywords: Compensation and Job Satisfaction on Employee Retention.